Anti-inflammatory, anticoagulant and antioxidant effects of aqueous extracts from Moroccan thyme varieties - Tarik Khouya; Mhamed Ramchoun; Abdelbassat Hmidani; Souliman Amrani; Hicham Harnafi; Mohamed Benlyas; Younes Filali Zegzouti; Chakib Alem (Asian Pacific Journal of Tropical Biomedicine, 2015)
Objective: To evaluate the anti-inflammatory, anticoagulant and antioxidant effects of aqueous extracts of thyme varieties from Moroccan. Methods: The aqueous extracts of tree medicinal plants [Thymus atlanticus (T. atlanticus), Thymus satureioides and Thymus zygis (T. zygis)] were screened for their antioxidant activity using 1,1-diphenyl-2-picrylhydrazyl radical-scavenging, ferric reducing antioxidant power assay, radical scavenging activity method, the inhibition of 2,2'-azobis (2-amidinopropane) dihydrochloride that induces oxidative erythrocyte hemolysis and thiobarbituric acid reactive substances assay. The anti-inflammatory activity of aqueous extracts was evaluated in vivo using croton oil-induced ear edema and carrageenan-induced paw edema in mice and rats, respectively. This extracts were evaluated in vitro for their anticoagulant activity at the different concentrations by partial thromboplastin time and prothrombin time activated. Results: All thyme varieties were found to possess considerable antioxidant activity and potent anti-inflammatory activity in the croton oil-induced edema. Administration of aqueous extracts of two varieties (50 mg/kg) (T. zygis and T. atlanticus) reduced significantly the carrageenan-induced paw edema similar to non-steroidal anti-inflammatory drug (indomethacin, 10 mg/kg). In partial thromboplastin time and prothrombin time tests, T. atlanticus and T. zygis extracts showed the strongest anticoagulant activity. In contrast, Thymus satureioides did not show the anticoagulant activity in these tests. Conclusions: All aqueous extracts possess considerable antioxidant activity and are rich in total polyphenol and flavonoid but they act differently in the process of inflammatory and coagulation studied. This study shows great variability of biological activities in thyme varieties.